Changes for Rebecca - Greene, Jacqueline Dembar (American Girl Pub., 2009)
Ten-year-old Rebecca Rubin is injured during a strike at the sweatshop where her uncle and cousin work when she tries to give a speech, while keeping a big secret from her family.